BIOELECTRIC ACTIVITY OF BRAIN NEURONS YOUNG MEN WITH SENSORINEURAL HEARING LOSS AND DEAFNESS - Olga Alexeevna Butova; Daria Anatol’evna Chernova (Наука. Инновации. Технологии, 2022)
Тhe article contains the analysis of change of bioelectric activity of brain neurons and content of calcium, potassium and magnesium in the peripheral blood of young men with sensorineural hearing loss and third degree of deafness of the city of Stavropol.